PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS SURAT RESMI SISWA KELAS VIII SMP NEGERI 4 PADANG - Sari, Wike Perdana; Nursaid, Nursaid; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study was to describe the influence of the discovery learning modelon essay writing official letter class VIII SMP Negeri 4 Padang. Data of this study is the result of the test writing official letter before and after treatment. Data collected by the test performance by providing employment to students in the form of test essay writing official letter. Essay writing official letter before and after treatment compared to see the effect of discovery learning model by using t-test formula This research is a quantitative experimental method. The results of this research are three: (1) skill bouquet of official letter class VIII SMP Negeri 4 Padang before using discovery learning model is the qualification Fair (C) with an average value of 62,60, (2) the exposition essay writing skills after using discovery learning class VIII SMP Negeri 4 Padang regency are in the qualification Very Good (BS) with an average value of 82,16, and (3) based on the t-test, concluded that there was a significant influence on the use of discovery learning model in teaching writing official letter essay class VIII SMPN 4 Padang.Â Kata kunci: pengaruh model discovery learning, menulis surat resmi